Evidence-based care for older people: where are we now and where to in the future?. (2nd January 2019) - Bennett, Michelle; Young, Jessica; Cartwright, Jade
ABSTRACT: Within contemporary health and social care for older people, it is widely accepted that best outcomes are achieved when health professionals collaborate to provide integrated, evidence-based and person-centred care. Though past studies have reported broad data about the nature of speech pathology services provided to older people, this study seeks increased understanding of factors that influence clinician choice of assessment and therapy approaches and clinician ability to provide evidence-based, interprofessional care. An online survey was used to gather data from 145 Australian speech-language pathologists working with people over the age of 65; in hospital, community, and residential aged care settings. Data reported were drawn from free text responses and analysed using thematic analysis. Results highlight the influence of clinician access to, and the dynamics of, an interprofessional team and support network as well as the availability of ongoing education on their ability to provide evidence-based, quality care. Participants emphasized the complexity of care provided to older people as necessitating team-based, coordinated care, and careful consideration of each clients' unique abilities and limitations. Though participants acknowledged the importance of reliability and validity in the selection of assessment and therapy approaches, they commented that assessment and therapy choice was most often determined by contextual factors. To facilitate best practice, there is a need for further research, teaching, and professional development that explicitly supports speech pathology involvement in interprofessional care teams, alongside consideration of an expanded model of evidence-based decision-making that further accounts for the influence of clinical context and team dynamics.